Media Advocacy for Environmental Protection in India: A Library-Based Review of Science Communication and Sustainable Development - Sheik Mohamed; Nirmala M; K. Prabakaran (International Journal of Science and Society (IJSS), 2026)
Environmental protection has become one of the most pressing challenges in India due to rapid industrialization, urbanization, climate change, and the depletion of natural resources. Effective communication strategies are therefore essential for increasing public awareness and supporting environmental policymaking. This study aims to examine the role of media advocacy in promoting environmental protection through a library-based review of scholarly literature. The study employed a qualitative Library-Based Search (LBS) approach by systematically reviewing books, peer-reviewed journal articles, government reports, and publications from international organizations. The collected literature was analyzed using thematic analysis to identify recurring patterns related to environmental communication, public participation, and policy advocacy. The findings indicate that both traditional and digital media significantly contribute to environmental awareness, climate change communication, citizen engagement, and the success of environmental campaigns in India. Nevertheless, challenges including misinformation, commercial interests, political influence, limited rural media coverage, and insufficient environmental journalism continue to hinder effective communication. This study concludes that strategic, evidence-based, and ethical media advocacy can strengthen environmental literacy, enhance public participation, and support sustainable environmental governance. The findings also provide practical insights for policymakers, media practitioners, and environmental organizations seeking to improve science communication for sustainable development.